The effect of pH on glucoamylase production, glycosylation and chemostat evolution of Aspergillus niger - Wallis, Gregg L.F.; Swift, Richard J.; Atterbury, Robert J.; Trappe, Susanne; Rinas, Ursula; Hemming, Frank W.; Wiebe, Marilyn G.; Trinci, Anthony P.J.; Peberdy, John F. (Elsevier, 2001)
The effect of ambient pH on production and glycosylation of glucoamylase (GAM) and on the generation of a morphological mutant produced by Aspergillus niger strain B1 (a transformant containing an additional 20 copies of the homologous GAM glaA gene) was studied. We have shown that a change in the pH from 4 to 5.4 during continuous cultivation of the A. niger B1 strain instigates or accelerates the spontaneous generation of a morphological mutant (LB). This mutant strain produced approx. 50% less extracellular protein and GAM during both chemostat and batch cultivation compared to another strain with parental-type morphology (PS). The intracellular levels of GAM were also lower in the LB strain. In addition, cultivation of the original parent B1 strain in a batch-pulse bioreactor at pH 5.5 resulted in a 9-fold drop in GAM production and a 5-fold drop in extracellular protein compared to that obtained at pH 4. Glycosylation analysis of the glucoamylases purified from shake-flask cultivation showed that both principal forms of GAM secreted by the LB strain possessed enhanced galactosylation (2-fold), compared to those of the PS. Four diagnostic methods (immunostaining, mild methanolysis, mild acid hydrolysis and β-galactofuranosidase digestion) provided evidence that the majority of this galactose was of the furanoic conformation. The GAMs produced during batch-pulse cultivation at pH 5.5 similarly showed an approx. 2-fold increase in galactofuranosylation compared to pH 4. Interestingly, in both cases the increased galactofuranosylation appears primarily restricted to the O-linked glycan component. Ambient pH therefore regulates both GAM production and influences its glycosylation.